2005
DOI: 10.1074/jbc.m505741200
|View full text |Cite
|
Sign up to set email alerts
|

Pdx-1 Links Histone H3-Lys-4 Methylation to RNA Polymerase II Elongation during Activation of Insulin Transcription

Abstract: Expression of the insulin gene is nearly exclusive to the ␤ cells of the pancreatic islets. Although the sequence-specific transcription factors that regulate insulin expression have been well studied, the interrelationship between these factors, chromatin structure, and transcriptional elongation by RNA polymerase II (pol II) has remained undefined. In this regard, recent studies have begun to establish a role for the methylation of histone H3 in the initiation or elongation of transcription by pol II. To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 37 publications
9
99
1
Order By: Relevance
“…Interestingly, although Pdx1 itself does not appear to have intrinsic abilility to either modify histones or directly alter chromatin structure, its depletion in β cell lines results in the loss of histone H3-Lys4 dimethylation (a mark of active, open chromatin) at the insulin gene. This result may be secondary to the recruitment of the histone methyltransferase Set7/9 by Pdx1 [147]. Similarly, the glucose-stimulated increase in histone H4 acetylation (another marker of active, open chromatin) at the insulin gene in both cell lines and islets by Pdx1 is consistent with its recruitment of the histone acetyltransferase p300 [145,153,154].…”
Section: Mechanisms Of Transcriptional Regulation By Pdx1mentioning
confidence: 64%
See 2 more Smart Citations
“…Interestingly, although Pdx1 itself does not appear to have intrinsic abilility to either modify histones or directly alter chromatin structure, its depletion in β cell lines results in the loss of histone H3-Lys4 dimethylation (a mark of active, open chromatin) at the insulin gene. This result may be secondary to the recruitment of the histone methyltransferase Set7/9 by Pdx1 [147]. Similarly, the glucose-stimulated increase in histone H4 acetylation (another marker of active, open chromatin) at the insulin gene in both cell lines and islets by Pdx1 is consistent with its recruitment of the histone acetyltransferase p300 [145,153,154].…”
Section: Mechanisms Of Transcriptional Regulation By Pdx1mentioning
confidence: 64%
“…Our laboratory has demonstrated that in the absence of Pdx1, the RNA polymerase II complex continues to be recruited to the insulin promoter, but transcriptional elongation by the complex is impaired [68]. Consistent with this observation, it appears that Pdx1 is necessary to ensure that the Ser5-phosphorylated isoform (the "initiation isoform") is appropriately converted to the Ser2-phosphorylated isoform (the "elongation isoform") [147]. These findings raise the possibility that the linkage between the Pdx1 transcriptional complex and the basal transcriptional machinery may involve an as yet unidentified kinase.…”
Section: Mechanisms Of Transcriptional Regulation By Pdx1mentioning
confidence: 84%
See 1 more Smart Citation
“…For example, Set7/9 interacts with Pdx1, an insulin transactivator, and catalyzes Pdx1 methylation. Although the interaction of Pdx1 with Set7/9 is able to recruit Set7/9 to histone H3 and induce H3K4 methylation (28,29), the methylation of Pdx1 is not directly associated with changes in Pdx1 function. In addition, although the methylation of DNMT1 leads to a decrease in the half-life of DNMT1, this modification is also not directly related to changes in DNMT1 methyltransferase activity (21,30).…”
Section: Discussionmentioning
confidence: 99%
“…p300 or CBP overexpression did not rescue the inhibition of PDX-1 transactivation by SREBP-1c (data not shown). Frances et al (49) have reported that PDX-1 physically associates with and recruits the H3-K4 methyltransferase SET9 to the insulin gene. Interaction of PDX-1 with SET9 may be required for the transactivation of the Pdx-1 promoter, and SREBP-1c may squelch the recruitment of SET9 to PDX-1.…”
Section: Discussionmentioning
confidence: 99%